2017
DOI: 10.1002/cite.201600119
|View full text |Cite
|
Sign up to set email alerts
|

Vom Laborkuriosum zum kontinuierlichen Prozess: Die Entwicklung thermomorpher Lösungsmittelsysteme

Abstract: Die homogene Katalyse zeichnet sich gegenüber der heterogenen Katalyse durch höhere Selektivität und Aktivität bei gleichzeitig milderen Reaktionsbedingungen aus; die Abtrennung der teuren Übergangsmetallkatalysatoren von den Reaktionsprodukten ist jedoch schwierig. Temperaturgesteuerte Lösungsmittelsysteme, die bei geringer Temperatur in zwei Phasen vorliegen und bei Temperaturerhöhung ein homogenes, einphasiges Lösungsmittelsystem ausbilden, ermöglichen eine Reaktionsführung ohne Stofftransportlimitierungen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
(24 reference statements)
0
13
0
1
Order By: Relevance
“…The selectivity to one or more of the possible skeletal structures can be adjusted to some extent by using additives. Due to the highly non‐polar products, the catalyst can be separated from the products using a so‐called thermomorphic solvent system (TMS) …”
Section: 3‐dienesmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity to one or more of the possible skeletal structures can be adjusted to some extent by using additives. Due to the highly non‐polar products, the catalyst can be separated from the products using a so‐called thermomorphic solvent system (TMS) …”
Section: 3‐dienesmentioning
confidence: 99%
“…This can be achieved, for example, by extracting the product from the reaction mixture or by immobilizing the catalyst on a solid support or in a separate phase. The latter can be combined with the use of thermomorphic solvent systems (TMS) ,. This separation has to be carried out without any catalyst deactivation.…”
Section: Catalystsmentioning
confidence: 99%
“…[39] The advantages of TMSs compared with other recycling strategies for homogeneous transition-metal catalysts are the general applicabilityo fs tandard solvents and readily available catalyst systems(precursors and ligands). [45] Certainly,v ariousr eviews on the recovery of homogeneous catalysts exist that enumerate the large number of different recovery strategies. However,t he focus herein is on the description of TMSs, giving ah olistic and detailed descriptiono fT MSs by considering the physical background, as well as challenges (e.g.,p roduct purification and cross-dissolubility of the product) and opportunities for the application of those systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, these strategies usually require sophisticated solvents or specific catalysts . The advantages of TMSs compared with other recycling strategies for homogeneous transition‐metal catalysts are the general applicability of standard solvents and readily available catalyst systems (precursors and ligands) …”
Section: Introductionmentioning
confidence: 99%
“…In this context, Gaide et al , successfully demonstrated the Pd/DTBPMB‐catalyzed methoxycarbonylation of UME with high yields of the desired diester using a thermomorphic solvent system (TMS) to recycle the homogeneous catalyst. Thus, a temperature‐dependent miscibility gap enables phase separation at low temperature and an efficient reaction without mass transport limitations at elevated temperature .…”
Section: Introductionmentioning
confidence: 99%